The morphology and biology of the trematode Gigantobilharzia acotylea (Digenea, Schistosomatidae) - Akramova, F.; Azimov, D.; Shakarboev, E. (Vestnik Zoologii, 2010)
Morpho-biological traits of the trematode Gigantobilharzia acotylea Odhner, 1910 at all stages of ontogeny are studied. Mollusks Physa fontinalis and Anisus spirorbis widespread in the waterbodies of the Syrdarya River valley were found to be intermediate hosts of this trematode under natural and experimental conditions in Uzbekistan. Prevalence of infection of P. fontinalis and A. spirorbis by Gigantobilharzia spp. parthenitae and cercariae reached 0.4 and 0.3%, respectively. Experimentally, 100% of these mollusks were infected. The maturation of cercariae in intermediate hosts ranged from 23 to 44 days depending on temperature. The cercariae actively penetrated the skin of birds and reached maturity in 30-35 days. A complex of traits of various developmental stages, particularly cercariae necessary for the differentiation of the Gigantobilharzia spp. is suggested based on of the analysis of morpho-biological peculiarities of these trematodes.